Listening to strangers more than friends: how recommendations from close- (vs distant-) others influence consumption. (1st May 2023) - Dong, Meichen; Saini, Ritesh
Abstract : Purpose: This paper aims to investigate how recommendations from close- versus distant-others influence consumer preferences. This paper explores how the consumption setting (public vs private) differentially affects the relative weight given to recommendations from these two sources. Design/methodology/approach: Through five scenario-based experiments and an internal meta-analysis, this paper examines whether consumers are more likely to follow recommendations from distant- (vs close-) others in public consumption settings. As a test of the underlying process, this study also investigates the mediating role of distinctiveness-signaling motivation in why consumers overweight recommendations from distant others in public settings, and the moderating role of atypical product design. Findings: The findings of this study support the hypothesis that recommendations from distant-others have a greater impact on consumer preferences in public consumption contexts, as opposed to recommendations from close-others. This result can be attributed to the heightened salience of consumers' distinctiveness-signaling motives in public consumption contexts, leading them to prioritize exhibiting uniqueness over conforming to close-others' recommendations. However, this study also reveals that the presence of alternative sources of distinctiveness, such as atypically designed products, can mitigate this effect, leading consumers to seek conformity to close-others' recommendations even in public consumption contexts. Research limitations/implications: This research did not look into the possible culture impact on the nonconforming consumption behavior. Previous research indicates that in collectivist cultures, nonconformity and distinctiveness are valued less (Kim and Drolet, 2003). This may imply that even with provoked signaling motives, collectivist consumers may not exhibit divergence from close-others. In fact, they may do the exact opposite and possibly become even more conforming to recommendations from close-others. Practical implications: This research shed light on the business practice regarding word-of-mouth (WOM). Specifically, this research results suggest that for publicly consumed product, companies may need to seek a nontraditional WOM and use less WOM from consumer's close-others. Originality/value: Marketers often use referrals and recommendations from close-others to shape consumers' preferences. In contrast, this study shows that for publicly consumed products, consumers may diverge from conforming to their close-others.